Optimization of a method for the clinical detection of serum exosomal miR-940 as a potential biomarker of breast cancer - Gu, Zhiyun; Yin, Haojie; Zhang, Haiwei; Zhang, Hui; Liu, Xiaoyu; Zeng, Xiaohua; Zheng, Xiaodong (Frontiers in Oncology, 2022)
Serum exosomal microRNAs (miRNAs) are potential biomarkers for tumor diagnosis. Clinically, reverse transcription-quantitative polymerase chain reaction (RT−qPCR) can be used to determine the expression of exosomal miRNAs in the serum of breast cancer patients. The prerequisites for obtaining meaningful serum exosomal miRNA data of breast cancer patients include a suitable extraction method for exosomes and RT−qPCR data standardized by internal reference genes. However, the appropriate methods for the extraction of exosomes and the applicability of reference genes for analyzing exosomal miRNAs in breast cancer patients remain to be studied. This study compared the effects of three exosome extraction methods as well as the expression of exosomal miRNA in different initial serum amounts and at different serum states to identify the selection of the best method for serum exosome extraction. Five candidate reference genes including miR-16, miR-484, miR-1228, miR-191 and miR-423 for standardizing serum exosomal miRNAs were screened using five algorithms and were used for the quantification of serum exosomal miR-940. Significant downregulation of serum exosomal miR-940 expression in breast cancer was detected using miR-191 and miR-1228, whereas no significant down or up regulation was observed with miR-484, miR-423 and miR-16. Previous studies have shown that the expression level of miR-940 is downregulated in breast cancer tissues. The absolute quantitative results showed that miR-940 was significantly downregulated in breast cancer serum exosomes, which was consistent with the results from the analysis using miR-191 or miR-1228 as reference genes. Therefore, miR-191 and miR-1228 could serve as reference genes for the relative quantification of serum exosomal miRNAs. This finding indicated the importance of rigorously evaluating the stability of reference genes and standardization for serum exosomal miRNA expression. Moreover, the level of serum exosomal miR-940 in breast cancer could reflect the presence of lymph node metastasis and the status of HER2/neu, which indicates its potential as a biomarker for breast cancer metastasis. In summary, an optimized protocol for the detection of serum exosomal miR-940 as a breast cancer marker was preliminarily established.